A coral reef handbook a guide to the geology, flora and fauna of the Great Barrier Reef. - Mather, P. and Bennett, I., eds. (Chipping Norton, NSW Surrey Beatty and Sons Pty Limited, 1993)
Smithsonian contributions to knowledge; 241
Keywords: Great Barrier Reef; Natural history--Australia--Great Barrier Reef; Coral reef plants--Australia--Great Barrier Reef; Coral reef animals--Australia--Great Barrier Reef